Preparing students for university studies and beyond: a micro-credential trial that delivers academic integrity awareness. Issue 1 (2nd January 2019) - Ruddy, Christine; Ponte, Frank
ABSTRACT: Micro-credentials are making an impact on the university course curriculums. Industry partners have increasingly indicated that students exit university with inadequate 'soft skills' such as team work, leadership and digital literacy skills. Micro-credentials are now being viewed favourably as a platform to address this deficit in workplace skills. Universities are now expending considerable time identifying industry skill gaps to provide students with the attributes that will serve for a successful transition to the world of work. This article addresses the development of an academic integrity awareness micro-credential for new student entrants to university. The trial of this micro-credential provides students with foundational skills in understanding the academic world, subsequently providing the advantage required for a successful transition to industry.